The Students’ Perception of Teacher Roles and Rapport in Teaching Writing - Kris Uluelang; Rizal Akib (Qalam : Jurnal Ilmu Kependidikan, 2020)
This research was conducted to find out the students’ perception and expectation of teacher roles and rapport in teaching writing at Universitas Muhammadiyah Sorong. The method used is mixed-method approach by applying convergent parallel design. The instruments of the research were questionnaires and interview. It reveals that the students have a negative perception of their teacher roles; the teacher does not perform his roles as a motivator, resource, and feedback provider in teaching writing. Instead, the students need it. On the other hand, students have a positive perception of their rapport. They think that their teacher respects them and also friendly. Unfortunately, the good rapport does not influence the students’ perception of their teacher. The students still need a teacher to be a motivator, resource, feedback provider, empowerer, monitor of their learning, and role model. The teacher also has to be friendly and respects them to make a good rapport.